The Effect of Perceived Audit Quality on the Relationship between Other Comprehensive Income and Earnings Management for Listed Companies in Saudi Stock Exchange - Alkhorayef, Ibtihal Abdullah; Zaytoun, Mohamed Khames (Journal of Economic, Administrative and Legal Sciences, 2024)
This research aimed to study and test the relationship between other comprehensive income and earnings management, as well as the moderated impact of perceived audit quality on this relationship using a sample of non-financial companies listed on the Saudi Stock Exchange for the period from 2020 to 2022. In its theoretical part, the research concluded that other comprehensive income includes items of income and expenses that are not recognized in profits or losses statement in accordance with what is required or permitted by international financial reporting standards. Earnings management is the use of flexibility in accounting policies and personal estimates to influence accounting data in order to seek personal benefits or mislead users with financial data about the company's financial performance. Perceived audit quality expresses the level of quality that is expected from the point of view of stakeholders, and can be inferred from the auditor’s industry specialization, the audit firm size, audit fees, auditor rotation. In addition, the research in its applied part has shown that there is an inverse and significant relationship between the values of other comprehensive income items and earnings management for companies listed in the Saudi financial market. Other comprehensive income and earnings management for companies listed in the Saudi financial market if the company is audited by an audit office affiliated with one of the four major offices, meaning that the level of perceived audit quality significantly affects the relationship between other comprehensive income and earnings management for companies listed in the Saudi financial market.
Keywords: Earnings Management; Other Comprehensive Income; Perceived Audit Quality